Non-spike and spike-specific memory T cell responses after the third dose of inactivated COVID-19 vaccine - Huang, Ruoqiong; Ying, Liyang; Wang, Jiangmei; Xia, Jie; Zhang, Yanjun; Mao, Haiyan; Zhang, Ruoyang; Zang, Ruoxi; Le, Zhenkai; Shu, Qiang; Xu, Jianguo (Frontiers in Immunology, 2023)
During the COVID-19 epidemic, vaccination has become the most safe and effective way to prevent severe illness and death. Inactivated vaccines are the most widely used type of COVID-19 vaccines in the world. In contrast to spike-based mRNA/protein COVID-19 vaccines, inactivated vaccines generate antibodies and T cell responses against both spike and non-spike antigens. However, the knowledge of inactivated vaccines in inducing non-spike-specific T cell response is very limited. In this study, eighteen healthcare volunteers received a homogenous booster (third) dose of the CoronaVac vaccine at least 6 months after the second dose. CD4+ and CD8+ T cell responses against a peptide pool from wild-type (WT) non-spike proteins and spike peptide pools from WT, Delta, and Omicron SARS-CoV-2 were examined before and 1-2 weeks after the booster dose. The booster dose elevated cytokine response in CD4+ and CD8+ T cells as well as expression of cytotoxic marker CD107a in CD8+ T cells in response to non-spike and spike antigens. The frequencies of cytokine-secreting non-spike-specific CD4+ and CD8+ T cells correlated well with those of spike-specific from WT, Delta, and Omicron. Activation-induced markers (AIM) assay also revealed that booster vaccination elicited non-spike-specific CD4+ and CD8+ T cell responses. In addition, booster vaccination produced similar spike-specific AIM+CD4+ and AIM+CD8+ T cell responses to WT, Delta, and Omicron, indicting strong cross-reactivity of functional cellular response between WT and variants. Furthermore, booster vaccination induced effector memory phenotypes of spike-specific and non-spike-specific CD4+ and CD8+ T cells. These data suggest that the booster dose of inactive vaccines broadens both non-spike-specific and spike-specific T cell responses against SARS-CoV-2.